Decay dynamics of HIV-1 depend on the inhibited stages of the viral life cycle - Sedaghat, Ahmad R. (National Academy of Sciences, 2008)
The time to suppression of HIV-1 viremia to below the limit of detection of standard clinical assays is an important prognostic indicator for patients on highly active antiretroviral therapy (HAART). Recent clinical trials of the integrase inhibitor raltegravir have demonstrated more rapid viral decay than previously seen with reverse transcriptase (RT) or protease inhibitor-based regimens. Because of the therapeutic importance of drugs that target different steps in the virus life cycle, it is imperative to consider whether viral dynamics are affected by the stage of the viral life cycle at which an antiretroviral drug acts. We use a mathematical model to investigate the effects of various drug classes on the dynamics of HIV-1 decay and show that the stage at which a drug acts affects the dynamics of viral decay. We find that the drug class acting latest in the viral life cycle dictates the dynamics of HIV-1 decay. In general, we find that the later in the life cycle an inhibitor acts, the more rapid the decay in viremia, and we illustrate this by comparing the effect of RT and integrase inhibitors on viral dynamics. We conclude that the rapid decay observed in patients on integrase-inhibitor-containing regimens is not necessarily an indication of greater drug efficacy but rather an expected consequence of the fact that this drug acts later in the life cycle. We propose that clinically observed viral decay rates for HAART regimens should be evaluated in the context of the drug classes that are represented.